Teacher-Centered Learning and Creative Reflection Approaches in Deaf Islamic Education Learning - Hadi, Yulianto; Remanita, Yuan; Tao-Tao, Leo Lestere Mollaneda; Sunoko, Ahmad (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Islamic education learning for deaf students faces communication challenges, requiring an inclusive approach with visual media, sign language, and application-based educational technology. This method effectively improves understanding of abstract Islamic concepts, encourages active participation of students, and fosters collaboration between teachers and parents to support religious education that is more responsive to special needs. This Islamic education learning for deaf students aims to examine 1) the implementation of learning in character development and 2) to analyze the reflection of Islamic education learning for deaf students. The research uses a qualitative design and case study methodology conducted at SLB Negeri Campurdarat Tulungagung from August 10-24, 2024. Researchers collected data through documentation, in-depth interviews, and observation involving the principal, elementary and high school teachers, four deaf students, and an Islamic education teacher—the data analysis with triangulation of methods and sources to ensure accuracy. The results show that implementing character development and reflecting on Islamic education learning for deaf students can be successfully achieved through various approaches, making the learning material easier to convey and increasing students' motivation.